(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
The aim of the article is to reinterpret, half a century after Cinzio Violante’s study, the dossier on the ‘da Bariano/da Maleo’. From the analysis of these charters, as is well known, a historiographical season of absolute centrality in the Italian medieval studies began, aimed at defining forms and times of the processes of seigniorialisation and territorialisation. My purpose is to take a different angle of view. These same sources can be the basis for a reconsideration regarding the structures of kinship, the features and spaces of political action at the end of the 10th century during the 11th century.